STRATEGIC COMPETENCE DEVELOPED BY DEBATERS OF NON-ENGLISH DEPARTMENT STUDENTS - Amalia Rosdianingtyas; Rr. Hasti Robiasih (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aims to: 1) find out which types of communication strategies employed by debaters of Gadjah Mada University (EDS UGM) from Non-English department to develop their strategic competence, 2) describe how debaters of EDS UGM from non-English department develop their most useful communication strategies and 3) find out the factors affecting speaking performance of debaters of EDS UGM from non-English department in debate. This research employs discourse analysis adapting strategic competence model by Celce-Murcia (2007). This research focused on the communication strategies. It also covered the factors which affect debaters’ speaking performance in debate. The data were collected through observation and semi-structured interviews. The data were analyzed using Miles, Huberman, and Saldana’s flow model of qualitative data research which included transcription and data reduction. Data is reduced through coding and classification. The findings revealed that stalling or time-gaining strategies were used 52,10%, achievement or compensatory strategies were used 34,04% and followed by self-monitoring strategies which appeared 14,89%. Furthermore, the findings also showed that factor of performance conditions is the most frequent factor which affect debaters’ speaking performance. This factor is followed by other factors such as affective factors, topical knowledge and feedback during speaking activities.